EDITORIAL: After all, what sets us apart from other nurses and other professionals? - Maria Manuela Martins (Associação Portuguesa dos Enfermeiros de Reabilitação, 2021)
There is no doubt that we exist, that we have specific training, within an academic framework, that we are present in the practice of care, that we show results of our interventions, and this has been evident in the studies we have published, but what makes us different? Is it the techniques, the concepts, the knowledge, or all this?